Bone mineral content and density in professional tennis players - Calbet, J. A.; Moysi, J. S.; Dorado, C.; Rodriguez, L. P. (Calcified Tissue International, 1998)
Total and regional bone mineral content (BMC) as well as lean and fat mass were measured in nine male professional tennis players (TPs) and 17 nonactive subjects; dual-energy X-ray absorptiometry (DXA) was used for measuring. The mean (+/-SD) age, body mass, and height were 26 +/- 6 and 24 +/- 3 years, 77 +/- 10 and 74 +/- 9 kg, and 180 +/- 6 and 178 +/- 6 cm for the TP and the control group (CG), respectively. The whole body composition for BMC, lean mass, and fat of the TP was similar to that observed in the CG. The tissue composition of the arms and legs was determined from the regional analysis of the whole-body DXA scan. The arm region included the hand, forearm, and arm, and was separated from the trunk by an inclined line crossing the scapulo-humeral joint. In the TP, the arm tissue mass (BMC + fat + lean mass) was about 20% greater in the dominant compared with the contralateral arm because of a greater lean (3772 +/- 500 versus 3148 +/- 380 g, P < 0.001) and BMC (229.0 +/- 43.5 versus 188.2 +/- 31.9 g, P < 0.001). In contrast, no significant differences were observed either in BMC or BMD between arms in the CG. Total mass, lean mass, and BMC were greater in the dominant arm of the TP than in the CG (all P < 0.05). In the TP, BMD was similar in both legs whereas in the CG, BMD was greater in the right leg. Lumbar spine (L2-L4) BMD, adjusted for body mass and height, was 15% greater in the TP than in the CG (P < 0.05). Femoral neck BMDs (femoral neck, Ward's triangle, greater trochanter, and intertrochanteric regions) adjusted for body mass and height were 10-15% greater in the TP (all P < 0.05). Ward's triangle BMD was correlated with the maximal leg extension isometric strength (r = 0. 77, P < 0.05) even when adjusted for body mass (r = 0.76, P < 0.05) and height (r = 0.77, P < 0.05). In summary, the participation in tennis is associated with increased BMD in the lumbar spine and femoral neck. These results may have implications for devising exercise strategies in young and middle-aged persons to prevent involutional osteoporosis later in life.